Restructuring the Criminal Warning Mechanism to Prioritize the Best Interests and Future of Children - Gabryella, Alyna; Aprlianda, Nurini; Endrawati, Lucky (IJBLE Scientific Publications Community Inc., 2025)
The designation of a warning as the principal punishment in Article 72 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System raises normative issues that conflict with the purpose of sentencing and the principle of the best interests of the child. This study employs a normative juridical method with a comparative approach, examining the procedure for issuing warning sanctions in Queensland, Australia. The analysis reveals that issuing warnings through a formal judicial process has the potential to cause psychological trauma and social stigma for children, thereby hindering their social reintegration. Consequently, there is a need to reconstruct the warning mechanism to be more oriented toward the best interests and future of children, while also strengthening legal protection for minors within Indonesia's criminal justice system.